FITOREMEDIASI TUMBUHAN AIR KIAMBANG (Salvinia molesta) PURUN TIKUS (Eleocharis dulcis) DAN PERUPUK (Phragmites karka) SEBAGAI ALTERNATIF PENGOLAHAN LIMBAH CAIR KARET - Norhidayah Norhidayah; Dini Sofarini; Yunandar Yunandar (EnviroScienteae, 2014)
The purpose of this study 1) assess the ability of aquatic plants Salvinia molesta, Eleocharis dulcis and Phragmites karka in reducing pollutant effluent, Zinc, DO, temperature, pH, BOD, COD, TSS, Turbidity  and Ammonia (NH3) in the rubber industry wastewater, 2) compare the water potential of plants to absorb pollutants wastewater rubber; 3) assess the status of the marine environment of rubber wastewater ponds to three (3) water treatment plant, the heavy metals zinc (Zn) in liquid waste rubber. The results of the study resulted in plant water Purun Rat able to reduce BOD by 64%, COD by 17% and Turbidity by 80%, water kiambang able to lower Zinc by 49% and TSS by 70%, water plant perupuk able to reduce ammonia (NH3) by 23%. Stable temperature and pH value in each pool plant installation, the results of research conducted in this value in the effluent water quality rubber has not met the quality standard of waste according to Government Regulation No. 8 of 2001 concerning Management of Water Quality and Water Pollution Control. The results of the study resulted in plant water Purun Rat able to reduce BOD5 by 64%, COD) by 17% and Turbidity by 80%, water kiambang able to lower Zinc by 49% and TSS by 70%, water plant perupuk able to reduce ammonia (NH3) by 23%. Stable temperature and pH value in each pool plant installation, the results of research conducted in this value in the effluent water quality rubber has not met the quality standard of waste according to Government Regulation No. 8 of 2001 concerning Management of Water Quality and Water Pollution Control.